2015
DOI: 10.1194/jlr.m057794
|View full text |Cite
|
Sign up to set email alerts
|

Anacetrapib reduces (V)LDL cholesterol by inhibition of CETP activity and reduction of plasma PCSK9

Abstract: High plasma levels of (V)LDL cholesterol [(V)LDL-C] and TGs, as well as low levels of HDL cholesterol (HDL-C), are important risk factors for cardiovascular diseases. The standard treatment for the reduction of cardiovascular disease risk is statin therapy aiming to reduce plasma (V) LDL-C. However, a substantial residual risk remains despite statin treatment. This has prompted the search for secondary treatment targets ( 1, 2 ). Prospective epidemiological studies indicate HDL-C as a potential target ( 3 ). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…The ability of anacetrapib to reduce plasma levels of PCSK9 has now been confi rmed in a study of CETP-expressing APOE*3-Leiden mice published in this issue of the Journal of Lipid Research ( 25 ). In this study, the investigators found that administration of anacetrapib decreased hepatic expression and plasma levels of PCSK9 and increased hepatic LDL receptor levels not only in animals expressing CETP, but also in APOE*3-Leiden mice that do not express CETP.…”
mentioning
confidence: 57%
“…The ability of anacetrapib to reduce plasma levels of PCSK9 has now been confi rmed in a study of CETP-expressing APOE*3-Leiden mice published in this issue of the Journal of Lipid Research ( 25 ). In this study, the investigators found that administration of anacetrapib decreased hepatic expression and plasma levels of PCSK9 and increased hepatic LDL receptor levels not only in animals expressing CETP, but also in APOE*3-Leiden mice that do not express CETP.…”
mentioning
confidence: 57%
“…In contrast to our findings, other CETP inhibitors were shown to reduce PCSK9 expression in vitro, in mice and monkeys. [38][39][40][41] Additional research will be needed to determine whether changes in PCSK9 levels result from a modulation of the canonical sterol regulatory elementbinding protein 2 transcription factor pathway or from off-target effects of torcetrapib.…”
Section: Discussionmentioning
confidence: 99%
“…Однако завершившиеся рандомизированные, клинические исследования указывают на ограниченную пользу применения этих препаратов в комбинации со стандартной терапией для улучшения исходов у пациентов с высоким сердечно-сосудистым риском, несмотря на ожидаемую модификацию липидного профиля [24], что лишний раз подчеркивает сложности изучения биологии старения. Недавно был установлен дополнительный (оff-target) эффект CEPT-ингибиторов в отношении proprotein convertase subtilisin/kexin 9 (PCSK9) [25,26] и продемонстрирована метаболическая ассоциация между уровнями CETP и PCSK9 [27], что в аспекте обсуждаемой проблемы усиливает интерес к бурно развивающейся и активно изучаемой группе липид-модифицирующих препаратов -ингибиторам PCSK9, с которой связывают большие надежды в области профилактики ССЗ и снижения резидуального риска.…”
Section: генетические исследования сверхдолгожительстваunclassified